Differentiation between malignant and benign rectal tumors by dual-energy computed tomography - a feasibility study. (1st April 2019) - Al-Najami, Issam; Mahmoud Sheta, Hussam; Baatrup, Gunnar
Abstract: Introduction: To assess the performance of Dual Energy Computed Tomography (DECT) in the differentiation between benign and malignant tumors in the rectum. Material and methods: We enrolled 8 subjects with rectal tumors suspected to be an early rectal cancer during colonoscopy. All subjects underwent Computed Tomography (CT), Magnetic Resonance Imaging (MRI) and Endorectal Ultrasound (ERUS) for staging. Furthermore, all subjects underwent fast switching of tube voltage between 80 and 140 kVp DECT of the pelvis. The 8 subjects had histopathological verified benign adenomas after transanal endoscopic microsurgery resection (TEM). The 8 subjects were matched with 8 consecutively selected subjects with histopathologically verified malignant rectal tumors. The DECT images were analyzed to assess the difference between malignant and benign rectal tumors. All DECT images were reviewed by experienced radiologists. In each DECT scanning, we applied three regions of interest (ROIs) for the acquisition of the DECT unique quantitative parameters. The mean atomic mass (effective Z value), iodine concentration, dual energy ratio (DER) and dual-energy index (DEI) was determined in both groups. Results: The comparison of the 2 groups showed a significant difference in effective Z and a nonsignificant difference regarding iodine concentration, DER, and DEI in the two groups. Conclusion: Dual-energy CT demonstrated a difference in the mean atomic mass in benign colorectal tumors in comparison to malignant colorectal tumors.